V4 fejlesztési bank - jövőkép 2020 után - Zágonyi Ádám (Geopolitikai szemle, 2019)
After 2020, the new fiscal cycle of the European Union will not only shift the emphasis, but the size of available resources will also be reduced as a result of Brexit. These issues will have a serious impact on Hungary as well, since the sources of the development type so far will be much less available to our country. Improvement and further development of infrastructure between countries is a prerequisite for V4’s economic ties. Therefore, shrinking resources would require new solutions. To remedy the “lack of money”, the V4 Group will set up a development bank. The main task of this V4 development bank will be to provide with much better credit-condition for countries than the market. The question is how will it solve and how can it develop a favorable external resource structure in addition to its own resources and how to optimize project. This is a multi-tasking complex question that requires some fiscal and partly monetary resources. Regional banks of this kind have several European and international examples. The following is an example of what might be the most suitable for our country with any changes. Whether it is an Asian-style big bank or a North European development bank will be a good example; The main expectation is that the bank will be able to lend in a positive way and the country will not “run into” another PPP unfavorable lending cycle. In addition, it can be stated that, after examining international examples, taking into account regional and regional specificities is indispensable. A bank serving regional goals, as the characteristics of the past and the challenges of the future, must be aware of the right answers and the creation of favorable development conditions.